Efektivitas Implementasi Desain Pembelajaran dalam Menunjang Kesuksesan Pembelajaran di SDN Kedaung Wetan 5 - Magdalena, Ina; Ramadini, Cantika; Melati, Suci (Lembaga Yasin AlSys, 2023)
The learning process can be successful, if the teacher has views that are in line with his philosophy, meaning that the success of the teacher in teaching can be seen from the extent to which the teacher applies the plan in the implementation of learning, so that the indicators set in the lesson plan are well absorbed by students. The method used in this research is a qualitative approach research method. Qualitative research is conducted to answer research according to problems that occur in the field where the research is carried out. The author uses data collection techniques in the form of observation and interviews with teachers at SDN Kedaung Wetan 5 Tangerang City. Based on the data and research results as well as analysis to draw conclusions the authors use the